Magnetoencephalography with temporal spread imaging to visualize propagation of epileptic activity. Issue 5 (May 2017) - Shibata, Sumiya; Matsuhashi, Masao; Kunieda, Takeharu; Yamao, Yukihiro; Inano, Rika; Kikuchi, Takayuki; Imamura, Hisaji; Takaya, Shigetoshi; Matsumoto, Riki; Ikeda, Akio; Takahashi, Ryosuke; Mima, Tatsuya; et al.
Highlights: Our novel method can show the spatiotemporal spread pattern of epileptic activity. The reproducibility of its propagation pattern can be statistically confirmed. The pattern was compared with that of FDG-PET hypometabolism in clinical cases. Abstract: Objective: We describe temporal spread imaging (TSI) that can identify the spatiotemporal pattern of epileptic activity using Magnetoencephalography (MEG). Methods: A three-dimensional grid of voxels covering the brain is created. The array-gain minimum-variance spatial filter is applied to an interictal spike to estimate the magnitude of the source and the time (Ta) when the magnitude exceeds a predefined threshold at each voxel. This calculation is performed through all spikes. Each voxel has the mean Ta () and spike number (Nsp ), which is the number of spikes whose source exceeds the threshold. Then, a random resampling method is used to determine the cutoff value of Nsp for the statistically reproducible pattern of the activity. Finally, all the voxels where the source exceeds the threshold reproducibly shown on the MRI with a color scale representing . Results: Four patients with intractable mesial temporal lobe epilepsy (MTLE) were analyzed. In three patients, the common pattern of the overlap between the propagation and the hypometabolism shown by fluorodeoxyglucose-positron emission tomography (FDG-PET) was identified. Conclusions: TSI can visualize statistically reproducible patterns of the temporal and spatial spread of epileptic activity. Significance: TSI can assess the statistical significance of the spatiotemporal pattern based on its reproducibility.